Retrospective study to compare the effectiveness of minimally ınvasive microscopic unilateral laminotomy with microscopic bilateral laminotomy for bilateral decompression in the early postoperative period in 142 patients with single-level lumbar spinal stenosis - Gülensoy, Bülent; Şimşek, Serkan (My University, 2024)
BACKGROUND We aimed to compare the effectiveness of microscopic unilateral laminotomy for bilateral decompression (ULBD) and microscopic bilateral laminotomy for bilateral decompression (BLBD) in the early postoperative period among patients with single-level lumbar spinal stenosis (LSS). MATERIAL AND METHODS A retrospective cohort study was conducted on patients with LSS who underwent ULBD or BLBD between January 2020 and December 2023, including 94 patients who underwent ULBD and 58 who underwent BLBD. Patient demographics, comorbidities, smoking status, and data related to LSS were reviewed. Preoperative and postoperative assessments on day 10 included back pain visual analog scale (VAS), walking distance, and Odom criteria. Disability was evaluated using the self-assessment Oswestry Disability Index (ODI) preoperatively and on day 30. Additionally, wound infection, postoperative modified MacNab criteria, and pain (back, leg, and hip) were recorded. RESULTS Age and sex were similar in the 2 groups. Both surgeries significantly reduced low back pain, increased walking distance, and improved Odom category on day 10, compared with baseline (P<0.001 for all). A significant decrease in 30-day ODI, compared with baseline, was observed in both groups (P<0.001 for both). The ULBD group had a significantly higher percentage of patients with wound infection (P=0.014); however, the ODI score among ULBD recipients was significantly lower (better) on day 30 (P=0.047). CONCLUSIONS ULBD may represent a less invasive, more effective, and safer surgical alternative than BLBD and classical laminectomy in patients with single-level LSS, but precautions are essential concerning wound infection.
Keywords: Lumbar Vertebrae; Spinal Canal; Spinal Stenosis